EVALUATING THE EFFECTIVENESS OF NURSING INTERVENTIONS ON PATIENT SATISFACTION AND HEALTH OUTCOMES: A MULTI-CENTER STUDY IN SAUDI ARABIA - Abeer Mohammed Saeed Saqer, Amal Mohammed Alshehri, Amal Mohammed Saad Alqarni, Amani Mubarak Albadour, Dalal Abdalrahman Alenazi, Maha Mohammed Alamri, Maram Obied Saad Alamri, Shuhrah Alwuayli Saeed Alshahrani, Yazeed Mohammed Alqahtani (Chelonian Research Foundation, 2022)
Nursing interventions play a crucial role in improving patient satisfaction and health outcomes. This study aims to evaluate the effectiveness of various nursing interventions on these two key variables in multiple healthcare centers across Saudi Arabia. A mixed-methods approach was employed, combining a retrospective analysis of patient records and a cross-sectional survey of patients and nurses. The study included 1,500 patients and 500 nurses from five major hospitals in different regions of Saudi Arabia. The data were analyzed using descriptive statistics, multiple regression, and content analysis. The results showed that patient-centered care, effective communication, and evidence-based practice were the most significant predictors of patient satisfaction and improved health outcomes. The qualitative findings revealed that nurses' empathy, cultural competence, and teamwork were essential factors in delivering high-quality care. The study highlights the importance of implementing targeted nursing interventions and provides recommendations for healthcare policy and practice in Saudi Arabia. Keywords: nursing interventions, patient satisfaction, health outcomes, patient-centered care, evidence-based practice, Saudi Arabia